A Multi-Tenancy Database Approach to Effective Emergency Preparedness and Mitigation - Henry, Ogbu Nwani (IJRDO -Journal of Computer Science Engineering, 2016)
Emergency managements’ sole idea is to reduce occurrences, reduce the intensity of occurrences or to safeguard lives and properties during emergency situations. Preparedness, Mitigation, Response and Recovery phases are four phases of emergency management. While Mitigation phase is concerned with actions taken to reduce the chances of an accident occurring through risk assessment or early attempts to make the consequences of an accident as small as possible, preparedness phase deals with every method applied to get ready for future imaginable incidents. They include developing systems, managing resources, developing scenarios and plans and engaging in realistic training. Emergency management agencies are in constant search of ways to enhance preparedness and mitigation phases to reduce the chances of accidents occurring. In this research, we present an architecture based on multi-tenancy which consolidates multiple databases from multiple emergency management agencies to improve access to emergency information, strategic planning and risk assessment thereby enabling easy development of emergency management systems (EMS), reducing cost of such development and also its operations.